A synthesis and review of exacerbated inequities from the February 2021 winter storm (Uri) in Texas and the risks moving forward. (1st January 2023) - Castellanos, Sergio; Potts, Jerry; Tiedmann, Helena; Alverson, Sarah; Glazer, Yael R; Robison, Andrew; Russo, Suzanne; Harmon, Dana; Ken-Opurum, Bobuchi; Weisz, Margo; Acuna, Frances; Stephens, Keri K; et al.
Abstract: A severe winter storm in February 2021 impacted multiple infrastructure systems in Texas, leaving over 13 million people without electricity and/or water, potentially $100 billion in economic damages, and almost 250 lives lost. While the entire state was impacted by temperatures up to 10 °C colder than expected for this time of year, as well as levels of snow and ice accumulation not observed in decades, the responses and outcomes from communities were inconsistent and exacerbated prevailing social and infrastructure inequities that are still impacting those communities. In this contribution, we synthesize a subset of multiple documented inequities stemming from the interdependence of the water, housing, transportation, and communication sectors with the energy sector, and present a summary of actions to address the interdependency of infrastructure system inequities.